Myocardial tissue engineering - Chen, Q. Z.; Harding, S. E.; Rai, Ranjana; Boccaccini, Aldo R. (Elsevier Inc., 2014)
In the pursuit of engineering a functional myocardium, studies integrating highly innovative research in stem cells and biomaterials development have opened new frontiers. Stringent properties like biocompatibility, ability to foster cells, biodegradability and mechanical compliance have been the norm for material selection. Fabrication techniques implemented individually or in conjunction have been used to fabricate scaffolds that best mimic the anisotropic nature of the cardiac extracellular matrix (ECM). Such biomimetic scaffolds provide topographical cues for contact guidance to align cells required to achieve synchronous electrophysiological coupling of the engineered myocardium to the native heart. Various functionalization strategies in tandem with scaffold fabrication designs and bioreactor studies have been undertaken to achieve vascularization in the engineered cardiac construct.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Biocompatibility; Biomaterials; Myocardial tissue engineering (MTE); Stem cells; Vascularization